REDUCTION IN ANXIETY SCORES FOLLOWING PROGGRESIVE MUSCLE RELAXATION THERAPY IN MDR TUBERCULOSIS - Lekatompessy, Meylan Frely; Lisum, Kristina; Soepardi, Soedibyo (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Anxiety is an ambiguous fear or concern, characterized by an emotional state devoid of a definite target, accompanied by sensations of uncertainty, powerlessness, isolation, and insecurity. This study is to examine the reduction in anxiety levels following progressive muscle relaxation therapy among drug-resistant tuberculosis patients in Ambon City in 2024. The research design utilized a pre-experimental one-group pre-test post-test methodology. The sample size consisted of 34 individuals who were selected through a comprehensive sampling methodology. We collected data using the HARS (Hamilton Anxiety Rating Scale) questionnaire. The findings indicated that the highest proportion of TBC-RO patients had moderate anxiety (55.9%), which subsequently diminished to mild anxiety (61.8%) following progressive muscle relaxation therapy. Patients with tuberculosis in Romania can considerably reduce their anxiety level by 34.2% following progressive muscle relaxation therapy (p value = 0.001). We observed a substantial reduction in anxiety levels before and after the progressive muscle relaxation therapy intervention, with a p-value of 0.001. Recommendation: Undertake additional research incorporating many factors that may influence the reduction of patient anxiety.